Management of concrete structures for long-term serviceability proceedings of the international seminar held at the University of Sheffield, England, UK on 13 November 1997 - Byars, Ewan A.; McNulty, Tony (Thomas Telford, 1997)
Presents the proceedings of the seminar organised by the Centre for Cement and Concrete at the University of Sheffield to bring together information on the issues concerning the management of many concrete structures. The themes of this book are: design construction, prediction and inspection; and strategies for maintenance and serviceability.